2015
DOI: 10.1149/2.0611506jes
|View full text |Cite
|
Sign up to set email alerts
|

Critical Link between Materials Chemistry and Cell-Level Design for High Energy Density and Low Cost Lithium-Sulfur Transportation Battery

Abstract: A materials-to-system analysis for the lithium-sulfur (Li-S) electric vehicle battery is presented that identifies the key electrode and cell design considerations from reports of materials chemistry. The resulting systems-level energy density, specific energy and battery price as a function of these parameters is projected. Excess lithium metal amount at the anode and useable specific capacity, electrolyte volume fraction, sulfur to carbon ratio and reaction kinetics at the cathode are all shown to be critica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
284
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 213 publications
(290 citation statements)
references
References 46 publications
5
284
0
1
Order By: Relevance
“…In the case of metallic lithium anodes, protection layers (polymer/solid electrolyte) are likely required for safety and stability reasons, which will also add yet undefined cost. Further cost studies can be found in the analysis by Eroglu et al 69 Safety aspects of lithium-sulfur batteries.-Dendrite formation is a well-known risk with metallic lithium anodes, leading to internal short circuits and safety hazards. A possible solution could be the use of a lithium-conducting solid electrolyte, acting as barrier to prevent dendrite formation and to block polysulfide reduction and deposition on the anode surface.…”
mentioning
confidence: 99%
“…In the case of metallic lithium anodes, protection layers (polymer/solid electrolyte) are likely required for safety and stability reasons, which will also add yet undefined cost. Further cost studies can be found in the analysis by Eroglu et al 69 Safety aspects of lithium-sulfur batteries.-Dendrite formation is a well-known risk with metallic lithium anodes, leading to internal short circuits and safety hazards. A possible solution could be the use of a lithium-conducting solid electrolyte, acting as barrier to prevent dendrite formation and to block polysulfide reduction and deposition on the anode surface.…”
mentioning
confidence: 99%
“…Recently, several studies have identified that the attainment of areal capacities as high as 4-8 mAh/cm 2 while minimizing the electrolyte content are the key factors in meeting these requirements. [1][2][3] The only currently commercialized Li-S battery has a significantly lower areal capacity of 2.5 mAh/cm 2 and operates in the presence of excess electrolyte, 4 necessitating significant technological breakthroughs to facilitate the possible use of Li-S batteries in the transportation sector. One of the main barriers to achieving such breakthroughs is the lack of fundamental understanding of the mechanism behind the operation of Li-S batteries.…”
mentioning
confidence: 99%
“…The negative electrode excess may have to be reduced to the order of 50-100%, according to at least one recent analysis. 8 There are compelling reasons to continue to focus on Li metal, however: it has the highest energy density of all the candidate negative electrode materials, and is likely to present fewer challenges for large-scale cell production compared to the alternative ''Li-ion-sulfur'' approach, which requires the use of either lithiated carbon or silicon, or lithium sulfide, as the lithium source -all of which are highly air-sensitive. In this paper, we present a novel method for visualising and quantifying the changes in cell resistance to demonstrate the limitation on cycle life caused by a low excess of the Li metal electrode in the Li-S system.…”
mentioning
confidence: 99%